A Longitudinal Investigation of the Relationship Between Gender Discrepancy Stress and Teen Dating Violence - Williams, Samantha (2020)
Gender discrepancy stress (GDS), or anxiety stemming from perceived nonconformity to traditional gender roles, has exhibited associations with numerous adverse physical and psychological health outcomes. Adolescents are particularly susceptible to socialization regarding prescribed gender role norms, and beliefs regarding appropriate behavior are often established during this key developmental stage. Previous studies have investigated the effects of GDS on deleterious health outcomes, yet causal inference has been limited due to cross-sectional data. The present study will aim to expand upon existing research by examining the longitudinal relationships between GDS, attitudes condoning violence, and physical teen dating violence (TDV). Data are drawn from a sample of male and female high school students (N=648) who completed self-report questionnaires annually over the course of four waves. Structural equation modeling was employed to test the effects of GDS on physical TDV perpetration and victimization, and latent difference scores were used to evaluate acceptance of violence (AoV) as a potential mediator. Findings indicate that an increase in GDS has a direct, positive effect on subsequent changes in physical TDV perpetration, while an increase in GDS has a negative effect on subsequent levels of physical TDV perpetration for females. Results did not reveal a significant link between GDS and physical TDV victimization for either gender, and there was no evidence that AoV mediated the relationship between GDS and physical TDV. These findings suggest that it may prove beneficial to integrate tailored gender socialization topics in the context of social norms within TDV interventions